IMPLEMENTASI PEMBELAJARAN BLANDED LEARNING PADA MASA PANDEMI COVID-19 DI MTS AL-QUDSIYAH KLOTOK PLUMPANG TUBAN - Sayyidatun Ni’mah; Nur Hasan; Dwi Fitri Wiyono (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
At this time at MTs Al-Qudsiyah Klotok Plumpang Tuban has implemented Blended Learning or better known at the school with the term combination, namely face-to-face or offline learning and online or online learning combined into one with face-to-face or online learning done twice in a week by implementing health protocols while online learning is carried out in a flexible way through online media. blended learning or this combination is applied because not all materials can be delivered online or online considering that not all students have the same access and ability to receive learning materials. Covid-19 or commonly referred to as corona is a very dangerous virus and its spread can develop rapidly so social distancing is needed to break the chain of spread of the covid-19 virus. implementation of blended learning during the covid-19 period, which is a learning process that has been planned during the covid-19 period by combining face-to-face learning (offline) with virtual learning (online). Kata Kunci: Implementation, Blended Learning, Covid-19